Class III beta-tubulin is constitutively coexpressed with glial fibrillary acidic protein and nestin in midgestational human fetal astrocytes: implications for phenotypic identity - Dráberová, Eduarda; Del Valle, Luis; Gordon, Jennifer; Marková, Vladimíra; Smejkalová, Barbora; Bertrand, Louise; de Chadarévian, Jean-Pierre; Agamanolis, Dimitri P; Legido, Agustin; Khalili, Kamel; Dráber, Pavel; Katsetos, Christos D (Journal of neuropathology and experimental neurology, 2008)
Class III beta-tubulin isotype (betaIII-tubulin) is widely regarded as a neuronal marker in developmental neurobiology and stem cell research. To test the specificity of this marker protein, we determined its expression and distribution in primary cultures of glial fibrillary acidic protein (GFAP)-expressing astrocytes isolated from the cerebral hemispheres of 2 human fetuses at 18 to 20 weeks of gestation. Cells were maintained as monolayer cultures for 1 to 21 days without differentiation induction. By immunofluorescence microscopy, coexpression of betaIII-tubulin and GFAP was detected in cells at all time points but in spatially distinct patterns. The numbers of GFAP+ cells gradually decreased from Days 1 to 21 in vitro, whereas betaIII-tubulin immunoreactivity was present in 100% of cells at all time points. beta-III-tubulin mRNA and protein expression were demonstrated in cultured cells by reverse-transcriptase-polymerase chain reaction and immunoblotting, respectively. Glial fibrillary acidic protein+/beta-III-tubulin-positive cells coexpressed nestin and vimentin but lacked neurofilament proteins, CD133, and glutamate-aspartate transporter. Weak cytoplasmic staining was detected with antibodies against microtubule-associated protein 2 isoforms. Confocal microscopy, performed on autopsy brain samples of human fetuses at 16 to 20 gestational weeks, revealed widespread colocalization of GFAP and betaIII-tubulin in cells of the ventricular/subventricular zones and the cortical plate. Our results indicate that in the midgestational human brain, betaIII-tubulin is not neuron specific because it is constitutively expressed in GFAP+/nestin+ presumptive fetal astrocytes.
Keywords: kultivované buňky; messenger RNA; vývojová regulace genové exprese; Astrocytes; Gestational Age; plod; Glial Fibrillary Acidic Protein; Nestin; Mice; fenotyp; Nerve Tissue Proteins; astrocyty; Gene Expression Regulation, Developmental; gestační stáří; Cells, Cultured; Phenotype; mozková kůra; RNA, Messenger; zvířata; Humans; Tubulin; vimentin; Cerebral Cortex; Intermediate Filament Proteins; proteiny nervové tkáně; myši; gliový fibrilární kyselý protein; tubulin; Fetus; proteiny intermediálních filament; nestin; Vimentin; lidé; Animals